Ganges Strategic Basin Assessment : A Discussion of Regional Opportunities and Risks - World Bank (Washington, DC, 2016)
The objective of the Ganges Strategic Basin Assessment (Ganges SBA) is to build knowledge and promote an open, evidence-based dialogue on the shared opportunities and risks of cooperative management in the basin. It is hoped that this will lead to greater cooperation in the management of this shared river system, beginning with a shift from information secrecy to information sharing. The key feature of this regional research is the development of a set of nested hydrological and economic basin models, along with targeted analyses on social vulnerability and climate change. The mosaic of information produced using these tools and approaches can be used to examine alternative scenarios across a range of possible Ganges futures.